Correlation and regression dependences between quantity and quality indicators depending on fertilizing of bird's-foot-trefoil with humate fertilizers - Boryana Churkova (Journal of BioScience and Biotechnology, 2019)
During the period of 2013-2015 in the experimental field of RIMSA-Troyan was conducted an experiment. The experimental design was a block with 4 replications with a plot size of 5 m2 of grassland with 'Targovishte 1' bird's-foot-trefoil cultivar. The following fertilizing variants were examined: control - null, phosphorus humate (3000 l'ha), boron humate (1600 l/ha) and molybdenum humate (1600 l/ha) and phosphorus humate (2500 l/ha) + boron humate (1000 l/ha) + molybdenum humate (1000 l/ha). Obtained correlation dependencies and regression equations are made between quantitative and qualitative indicators depending on fertilization with humate fertilizers. The crude protein content has been found to have high positive correlations with the percentage of leaves in the grassland (r = 0.8173) and the weight percentage of bird's-foot-trefoil (r = 0.7835), which allows the development of graphical regression models. There is a high correlation between the height of the plants and the relative share of the stems in the grassland (r = 0.8058), as well as between Feed units for growth and milk (r = 0.9457). The high coefficient of determination between the percentage share of bird's-foot-trefoil and the quantity of the stems R2 = 0.9087 determines the equation of the regression dependence between these two components (y = 1.2167x-65,001).